Digitisation in facilities management: A literature review and future research directions - Wong, Johnny Kwok Wai; Ge, Janet; He, Sean Xiangjian (Automation in construction, 2018)
Research into digital technology (DT) in construction practices has gained widespread attention. While the application of different DTs in facility management (FM) has been growing, to date, there is no holistic review of the various DT developments and research into FM. A total of 120 academic journal papers, conference proceedings and other technical notes published on the subject, mainly between 2004 and 2017, were reviewed in this paper. The applications of various major DTs, including 1) building information modelling (BIM), 2) reality capture technology (including 3D laser scanning, point cloud), 3) the Internet of Things (IoT) (including radio frequency identification (RFID) and sensor network technologies) and 4) geographic information system (GIS), were reviewed and scrutinised. The review identified a number of possibilities for future research into DT in FM, including, enhancing the interoperability of data, improving the accuracy of point cloud data for developing as-built models for existing facilities, and generating effective BIM/GIS asset database integration. It is hoped that this review and the future directions highlighted in this paper will assist researchers in identifying the areas where further research efforts are most required and in identifying which future directions would be most helpful for digital FM research. •Application of various digital technologies on facilities management were examined•Interoperability of data from as-designed to as-built data remains a key barrier•More efforts on improving data capturing technologies for “as-is” BIM is needed•Future work should improve spatial and geometric aspects of GIS-BIM integration•Enhancing the capability of RFID-based data storage and management is required